Bridging Unilamellar Nanosheets for High Performance Additive-Free Supercapacitor Electrodes - Gu, Feng (2016)
Conductive Co(OH)2 nanoporous electrode is developed by topochemically bridging unilamellar nanosheets with in situ formed coordination bonds. The high electrical conductivity and ligand-bridged nanoporous architecture endow the additive-free Co(OH)2 electrode with excellent capacitance, rate capability and an impressive cycling stability.